2001
DOI: 10.1258/0022215011907442
|View full text |Cite
|
Sign up to set email alerts
|

How common is hearing impairment in osteogenesis imperfecta?

Abstract: Hearing impairment has long been recognized as a common feature in osteogenesis imperfecta. The figures in some publications could be taken to imply that, with increasing age, the proportion of osteogenesis imperfecta patients with hearing impairment approaches 100 per cent. The incidence of hearing loss in a large survey of 1394 patients with osteogenesis imperfecta was examined. It was found that the most common age of onset was in the second, third and fourth decades of life. At the age of 50 approximately … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
35
0
3

Year Published

2003
2003
2019
2019

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 54 publications
(39 citation statements)
references
References 12 publications
1
35
0
3
Order By: Relevance
“…Up to 59% of adult OI patients have been reported to have progressive hearing loss in different populations [Seedorff, 1949;Smårs, 1961;Pedersen, 1984;Stewart and O'Reilly, 1989;Paterson et al, 2001;Kuurila et al, 2002]. In the present study, hearing loss was found in 32 patients (65.3%).…”
Section: Discussionsupporting
confidence: 45%
See 3 more Smart Citations
“…Up to 59% of adult OI patients have been reported to have progressive hearing loss in different populations [Seedorff, 1949;Smårs, 1961;Pedersen, 1984;Stewart and O'Reilly, 1989;Paterson et al, 2001;Kuurila et al, 2002]. In the present study, hearing loss was found in 32 patients (65.3%).…”
Section: Discussionsupporting
confidence: 45%
“…However, some patients present at onset with a predominantly sensorineural pattern [Pedersen, 1984;Garretsen et al, 1997;Kuurila et al, 2000Kuurila et al, , 2002. Hearing loss has been suggested to be more frequent in OI type I than in OI type IV [Sillence, 1981[Sillence, , 1988Paterson et al, 2001]. In our previous study, however, no correlation was found between the OI types and the presence, type, or severity of hearing loss [Kuurila et al, 2002].…”
Section: Introductionmentioning
confidence: 76%
See 2 more Smart Citations
“…About one-third of such patients are affected by the age of 30 and one-half by the age of 50, although the proportion affected does not change much after that age. Hearing impairment shows distinct familial trends, being common in some families and infrequent in others [32]. Cardiac valve dysfunction (aortic or mitral regurgitation) is a recognized but uncommon feature seen in people with OI, but the mechanistic relationship between the two remains unclear.…”
Section: Oi In Adultsmentioning
confidence: 99%